Implementation of Podcast Media in Fiqh Learning - Via Dina; Zulhijra; Ibnu Rozali (PAI RAFAH, 2026)
This research was inspired by the belief that education should not only aim for academic achievement but also focus on shaping students' character to be religious, tolerant, and moderate. At SD Muhammadiyah 18 Palembang, one of the flagship programs to realize this vision is the diniyah extracurricular activities. Through these activities, students are guided to strengthen their understanding of Islam while also practicing values of religious moderation. The programs include iqra' and Qur'an learning, prayer and hadith ctice, all of which are designed to encourage students to not only know the theory but also live it out in daily life. This study used a qualitative descriptive method with observations, interviews, and documentation. The findings show that diniyah extracurriculars contribute greatly to building moderation attitudes in students. Methods like reading, sima'i (listening), tahsin tilawah, and writing also enhance discipline, confidence, and responsibility. Support from schools, facilities, students, and parents has strengthened the program, although challenges such as time limitations and tutoring schedules still exist. Overall, diniyah extracurriculars serve as an effective model for nurturing a religious, tolerant, and nationally minded generation in Indonesia.